Strategi Pembelajaran Anak Berkebutuhan Khusus di Masa Pandemi Pada Setting Sekolah Inklusif (Studi Kasus: SMA Negeri 2 Bukittinggi) - Sintia Fadhillah Sari; Reno Fernandes; Eka Asih Febriani (Naradidik: Journal of Education and Pedagogy, 2022)
This study aims to find out what strategies are used by teachers in teaching children with special needs during the pandemic in an inclusive school setting at SMA Negeri 2 Bukittinggi. This research is a qualitative research with the type of case study research. The data in this study were analyzed using structural functional theory with the concept of AGIL (Adaptation, Goal Attainment, Integration, Latent Maintenance). This functional structural theory views society as a system consisting of elements that are interrelated and interdependent so that, if an element is not aware that they are a unit, it will make the system disorganized. The selection of informants was carried out by purposive sampling, namely as many as 15 teacher informants who teach in inclusive classes at SMA Negeri 2 Bukittinggi. Data collection was carried out by the methods of observation, interviews, and documentation. The results of this study indicate that the strategy used by teachers for children with special needs is to use individual learning for students, contributions from parents, and provide simple questions to students who experience these weaknesses.